The development of a training course for clubfoot treatment in Africa: learning points for course development - Smythe, T; Le, G; Owen, R; Ayana, B; Hansen, L; Lavy, C (BioMed Central, 2018)
Background: Clubfoot is a common congenital disorder that causes mobility impairment. There is a lack of trained mid-level personnel to provide clubfoot treatment in Africa and there is no standard training course. This prospective study describes the collaborative and participatory approach to the development of a training course for the treatment of clubfoot in children in resource constrained settings. Methods: We used a systems approach to evaluate the development of the training course. Inputs: The research strategy included a review of context and available training materials, and the collection of data on current training practices. Semi-structured interviews were conducted with seven expert clubfoot trainers. A survey of 32 international and regional trainers was undertaken to inform practical issues. The data were used to develop a framework for training with advice from two technical groups, consisting of regional and international stakeholders and experts. Process: A consensus approach was undertaken during workshops, meetings and the sharing of documents. The design process for the training materials took twenty-four months and was iterative. The training materials were piloted nine times between September 2015 and February 2017. Processes and materials were reviewed and adapted according to feedback after each pilot. Results: Fifty-one regional trainers from Africa (18 countries), 21 international experts (11 countries), 113 local providers of clubfoot treatment (Ethiopia, Rwanda and Kenya) and local organising teams were involved in developing the curriculum and pilot testing. The diversity of the two technical advisory groups allowed a wide range of contributions to the collaboration. Output: The resulting curriculum and content comprised a two day basic training and a two day advanced course. The basic course utilised adult learning techniques for training novice providers in the treatment of idiopathic clubfoot in children under two years old. The advanced course builds on these principles. Conclusion: Formative research that included mixed methods (both qualitative and quantitative) was important in the development of an appropriate training course. The process documentation from this study provides useful information to assist planning of medical training programmes and may serve as a model for the development of other courses.